Enhancing Medical Education: The Impact of Deliberate Practice on Learning Human Physiology - Júlia Silva Souza; Lavínia Penido Safe; Airton Martins da Costa Lopes; Augusto Scalabrini - Neto (University Library System, University of Pittsburgh, 2024)
Background: Simulation-Based Learning (SBL) has potential in health education, yet it remains underutilized at the undergraduate level. Active teaching methodologies, such as deliberate practice, are known to enhance skills like leadership, self-confidence, and teamwork. This study aimed to evaluate the medical students' perception of deliberate practice in learning Human Physiology at a private medical school in Brazil. Methods: An observational qualitative and quantitative study was conducted in 2022 and 2023 using an online questionnaire, including 198 participants. An inferential statistical analysis was conducted, using Fisher's exact test at a 0.05 level of significance, to assess the association between categorical variables. Results: Overall, students had a positive perception of deliberate practice. A significant proportion (66.8%) strongly agreed that they developed teamwork skills through the scenarios. Additionally, 83.7% strongly agreed that access to realistic simulation environments enhanced their learning. In terms of emotions, 67.9% felt motivated, while 37.8% experienced anxiety during the scenarios. The statistical analysis revealed a significant association between the sum scores of each section and the binary response ("yes" or "no") to the question "Do you like the practical classes of Human Physiology?" (p < 0.05), with the exception of the Negative Emotions sum. This indicates that higher section scores are associated with a greater likelihood of students liking the practical classes. Conclusion: The integration of deliberate practice into the Human Physiology curriculum has positively impacted students' learning and skill development. However, enhancements are needed to create a safer emotional environment for students.